Effective strategies for teaching in K-8 classrooms - Moore, Kenneth D.; Hansen, Jacquelyn Rae. (Thousand Oaks, [Calif.] ; London : SAGE, 2012)
This is a core textbook for general methods courses preparing teachers for key stages 1-4. Organized around a comprehensive model of teaching that includes foundations, planning implementation, and evaluation components, the strategies addressed in this volume are common to instruction in Key Stage 1-4 classrooms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Elementary school teaching -- United States; Middle school teaching -- United States; Effective teaching -- United States; Teacher effectiveness -- United States; Lesson planning; Classroom management